The Deleterious Health Consequences of COVID in United States Prisons - Mei, Xiaohan (American journal of criminal justice, 2024)
By January 2024, the COVID-19 pandemic claimed more than 1.1 million deaths in the United States (U.S.). People in prison are particularly vulnerable to COVID-19 as they have no ability to socially distance, secure masks, disinfect their environment or have as much access to tests or vaccinations as is available in the community. In addition, many of these individuals reside in crowded conditions with little ventilation, which makes the spread of the virus more likely. In this paper, we used data from two projects, including the UCLA Law COVID Behind Bars Data Project and the COVID Prison Project, and supplemented these with publicly available data to examine the number of deaths and infection rates caused by COVID-19 among people in prison and prison staff in the U.S., as reported by the population of those facilities. We found that the incidence of infections and death rates in prisons were affected by crowding, prison security type (maximum, medium, minimum, or mixed) and level of prison (state or federal). People in prison who were less likely to have as much human contact (e.g., maximum-security prisons) were also less likely to be afflicted with COVID-19. People in prison were twice as likely to be infected by COVID-19 but had a similar death rate compared to the general public. Prison overcrowding increased the infection rate. The most effective state health policy was to quarantine people who had close contact with confirmed, positive cases. Further, state prisons demonstrated a higher death rate compared to federal prisons. Greater efforts to ameliorate COVID-19 and similar pathogens should be directed at state prisons with lower-level security and prisons with closer contact with the community. Quarantining close-contacts and restricting movements were the most effective state-level responses to reduce infections in prisons during April 2020 to April 2022.